How does the invasive/native nature of species influence tadpoles' plastic responses to predators?. Issue 1 (31st May 2012) - Pujol‐Buxó, Eudald; San Sebastián, Olatz; Garriga, Núria; Llorente, Gustavo A.
<x xml:space="preserve">Abstract</x> Synthesis Anti–predator phenotypic plasticity is expected to be one of the major ecological forces driving survival and rapid evolution of prey facing new predators. This implies that biological invasions embody a perfect case for studying the tradeoffs and evolution of phenotypic plasticity. Our manuscript reports on high prey–predator specificity in these reactions and an evolutionary dissociation between behavioral and morphological plasticity in anurans. Each species displayed a particular set of tradeoffs between plastic responses and their costs, but interestingly we also detected mild patterns in combinations using introduced predators. Given the speed at which these evolutionary changes become noticeable and their potential in reducing predation risk, the role of antipredator phenotypic plasticity is expected to be crucial for population dynamics during biological invasions. Although the purely ecological impacts of biological invasions have been well studied, a less thorough effort has been made in terms of their evolutionary ecology. Previous studies show that anti‐predator phenotypic plasticity may be one of the major ecological forces driving survival and rapid evolution of prey facing new predators. In turn, this means that biological invasions embody a perfect case for studying the tradeoffs and evolution of phenotypic plasticity per se. Here, we studied the plastic responses of native (Pelodytes punctatus) and invasive (Discoglossus pictus) anurans facing a native (dragonfly Anax sp.) and two invasive (fish Gambusia holbrooki and crayfish Procambarus clarkii) predators. Marked responses were reported against the native predator from both the native and the invasive anuran, but they both responded mildly to the exotic predators as well. Native P. punctatus displayed a morphological reaction to invasive P. clarkii after scarcely 30 years of coexistence with this predatory crayfish and responded behaviorally to the invasive fish G. holbrooki. Invasive D. pictus reacted behaviorally to all predators, but unexpectedly only reacted morphologically to native Anax sp. All these results support high prey–predator specificity in these reactions and an evolutionary dissociation between behavioral and morphological plasticity in anurans. Each species displayed a particular set of tradeoffs between plastic responses and their costs, which is probably due to differences in ecological niche and evolutionary history, but interestingly we usually detected unexpected patterns in combinations using introduced predators. This suggests that perhaps singular plastic shifts usually occur when tadpoles face recently introduced species. Given the speed in which these evolutionary changes become noticeable and their potential in avoiding predation risk, this study supports that phenotypic plasticity might play an important role in population dynamics during biological invasions.